The effect of polypropylene fibres on the compressive strength, impact and heat resistance of self-compacting concrete. (June 2020) - Karimipour, Arash; Ghalehnovi, Mansour; de Brito, Jorge; Attari, Mohammad
Abstract: This paper intends to study the mechanical characteristics of self-compacting concrete (SCC) containing polypropylene fibres (PPF). 99 SCC specimens containing PPF were manufactured and tested. White 12-mm long PPF were used at 0%, 0.1%, and 0.3% by volume. The slump flow and T 500 were obtained on fresh SCC, while compressive strength, splitting tensile strength, impact resistance and heat resistance tests were performed to evaluate the SCC performance in the hardened state. To determine the effect of heat on SCC with and without PPF, the compressive and splitting tensile strengths of 28-day specimens placed at 250 °C for 8 h in an oven were evaluated. For the impact test, 50 mm, 100 mm and 300 mm cubic specimens were used. Also, a correlation was determined by trial and error to relate impact resistance with compressive strength, tensile strength, concrete age, temperature and PPF content. The results showed that, by increasing the volume of fibres in SCC, dispersion decreased. It was also observed that the use of 0.1% PPF significantly enhanced the compressive strength of SCC. Furthermore, the best performance in the splitting tensile strength, impact resistance and heat resistance tests was attained at 0.3% PPF.